건강신념모델을 기반한 소규모 산업장 생산직 남성근로자의 대사증후군 감소 프로그램 개발을 위한 요구사정 - 박윤희; 김두리 (한국직업건강간호학회지, 2018)
Purpose: This study aimed to comprehend the real context of metabolic syndrome-related factors of Korean male blue-collar workers from small-sized companies based on the health belief model. Methods: A total of 37 workers from three companies were interviewed, and three series of focus group interviews were conducted. Data were analyzed using deductive content analysis. Results: Data were classified into four categories: knowledge, perceived susceptibility and severity, perceived barriers, and beliefs. Knowledge referred to low knowledge level; perceived susceptibility and severity referred to unawareness of susceptibility and severity; perceived barriers referred to shift work, overtime work, and a social context including having no choice but to drink; and beliefs referred to believing that health promotion behaviors do not relate to preventing metabolic syndrome, believing that one cannot prevent metabolic syndrome oneself, and believing that professional help is required. Conclusion: To prevent and reduce the risk of metabolic syndrome among Korean male blue-collar workers, interventions should focus on strategies to increase metabolic syndrome-related knowledge and perceptions, social support, and self-efficacy for practicing health behaviors. In addition, it is necessary to develop policies for establishing a healthy drinking culture in companies.